Legal Protection of The Immunity Rights of Medical Personnel in Healthcare Service Practice in Indonesia - Gede Eka Rusdi Antara; Ni Nyoman Putri Purnama Santhi; Ni Putu Yuliana Kemalasari; I Putu Harry Suandana Putra (Westscience Press, 2026)
The right to health is a human right guaranteed under Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia, the fulfillment of which depends heavily on the role of medical personnel as providers of health services. In practice, medical personnel frequently face legal claims over medical risks that were in fact carried out in accordance with professional standards, as reflected in the case of dr. Dewa Ayu Sasiary Prawani, giving rise to concern and underscoring the urgency of clearly and definitively regulating the immunity rights of medical personnel. This study aims to analyze the legal regulation of the immunity rights of medical personnel under Indonesian legislation, its implementation in facing legal claims over medical risk, and the legal remedies available to protect it. The study uses a normative juridical method that is descriptive-analytical in nature and prescriptive in form, through statutory, conceptual, and case approaches, grounded in the theory of the rule of law, the theory of legal protection, and the theory of legal certainty. The results show that Law Number 17 of 2023 on Health regulates the immunity rights of medical personnel, health workers, and hospitals through Articles 273, 440, 308, 310, and 192, which are conditional (qualified immunity) rather than absolute. Its implementation is realized through the establishment of the Professional Disciplinary Council (Majelis Disiplin Profesi) as a primum remedium mechanism, while legal protection efforts are realized through eight complementary instruments, ranging from strengthening regulations to developing alternative dispute resolution, although legal certainty still needs to be substantively strengthened.